(3ZGjI GdSQhQ TQM OjhGf GdTPhQs - (3Ydj Hf eMeO Hf CjOeQ GdLdOcqj , YR GdOjf J (B742 (3g` s
(3ChdgG (B:s
(3Chdg eHJhQ hjHOC ef(B: (3hKGfjgeGJ Cf GdebGQfI YOGhI eMbbI dG SjeG eMGb GdbeQ hbQGfg HGdTeS s
(3BNQgG (B:s
(3Je GdcJGH HYhf GdhGMO GdhgGH s
(3GdLRA GdQGHY ef JbSje GdeNWhW jHOC HJQbje LOjO (B1 (3Edi (B143s
(3hgh HNW eZGjQ(B: (3fSN ebQhAs
(3GdfSNI HgG MhGTs
(3OjhGf GdTPhQ GdeTQhM gh dCHj GdMSf Ydi Hf ehSi Hf Ydi GdCfOdSi GdLjGfi J (B593 (3g` s
(3ai HOGjI GdfSNI agQSJ ai (B4 (3UaMGJ s
(3hgh eQJH Ydi GdMQha s
Keywords: (3GdcjejGA h GdWHjYjGJs